Combined platelet count with sCD163 and genetic variants optimizes esophageal varices prediction in cirrhotic patients. Issue 1 (19th December 2012) - Yang, Ying‐Ying; Hou, Ming‐Chih; Lin, Ming‐Wei; Chen, Ping‐Hsien; Liao, Wei‐Chih; Chu, Chi‐Jen; Lin, Han‐Chieh
Abstract Background and Aim Endoscopic screening for esophageal varices (EVs) is expensive and invasive. Besides traditional noninvasive markers, we explore additional candidate markers including portal hypertension serum marker‐soluble CD136 (sCD163) and genetic variants of splanchnic vasodilatation and revascularization pathways for prediction of EVs in cirrhotic patients. Methods A total of 951 cirrhotic patients without history of variceal bleeding and an independent validation cirrhotic cohort were enrolled to evaluate the association between the presence of EVs and patients' clinical and genetic characteristics. Results Cirrhotic patients with EVs had higher serum sCD163 and heme oxygenase‐1 (HO‐1) level, which was positively correlated with the number of risk alleles of HO‐1 (S, A), vascular endothelial growth factor (VEGF [G, T]) and VEGF receptor‐2 (VEGFR2 [Ile]) genes, than those without EVs. Multivariate analysis showed that EVs in cirrhotic patients was predicted by low platelet count, high sCD163 level, splenomegaly, HO‐1 AS and the VEGF GT risk haplotypes. Additive effects in relation to predict EVs were observed in the simultaneous presence of HO‐1 AS and VEGF GT risk haplotypes. Combining low platelet count with high sCD163/risk haplotypes significantly increased the predictability of EVs. Furthermore, cirrhotic patients carrying both HO‐1 AS and VEGF GT risk haplotypes had lower probability of being free of EVs bleeding compared to patients without above risk haplotypes. Conclusions This study suggested that high sCD163 levels and genetic risk variants are additional markers that can be combined with low platelet count to optimize assessment of EVs and bleeding in cirrhotic patients.